ANALISIS PEMAHAMAN KONSEP DAN KEMAMPUAN PEMECAHAN MASALAH PERBANDINGAN TRIGONOMETRI DITINJAU DARI GAYA BELAJAR SISWA SMA NEGERI 1 BANDA NEIRA - Shafriaty Kepa (PEDAMATH: Journal on Pedagogical Mathematics, 2019)
The research was descriptive research with qualitative approach which aimed at describing concept understandings and problem solving abilities of the students of class XI at SMAN 1 Banda Neira in solving trigonometry comparison problem based on the students’ learning styles, namely visual, auditory, and kinesthetic. The conclusion based on the test and interview results are: (1) Visual subject: Stating definition smoothly and thinking with focused eyes seeing in the question sheet, illustrating picture and using two way. Understanding the problem by reading question once silently, stating formula while thinking with your eyes closed like remembering something with a visual description. (2) Auditory subject: Stating definition clearly while thinking by moving lips, illustrating picture and using one way. Understanding the problem by reading question twice with a loud voice, stating formula by thinking like remembering information known by bowing face down. (3) Kinesthetic subject: Stating definition clearly, revealing slowly while tapping pen on the question sheet, illustrating picture and using two way. Understanding the problem by reading question three times silently and using finger to point while lifting the question sheet, stating formula with slowly while pointing at the image and symbol with finger.